2007
DOI: 10.1002/asi.20649
|View full text |Cite
|
Sign up to set email alerts
|

How is science cited on the Web? A classification of google unique Web citations

Abstract: Although the analysis of citations in the scholarly literature is now an established and relatively well understood part of information science, not enough is known about citations that can be found on the Web. In particular, are there new Web types, and if so, are these trivial or potentially useful for studying or evaluating research communication? We sought evidence based upon a sample of 1,577 Web citations of the URLs or titles of research articles in 64 open-access journals from biology, physics, chemist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 36 publications
1
31
0
1
Order By: Relevance
“…Vaughan and Shaw's (2005) follow-up study used their 2003 scheme to classify journal articles from four fields. Kousha and Thelwall (2007) sampled web citations to open-access journals in four fields (biology, physics, chemistry, and computing). Jepsen, Seiden, Ingwersen, Björneborn, and Borlund (2004) classified content from URLs containing specific terms related to plant biology into six categories: scientific, with research-related content (e.g., research articles, preprints); scientifically related (e.g., researchers' CVs); teaching (e.g., textbooks, tutorials, student papers); low grade, which was material that did not belong with the previous groups but was related to the searched topic (e.g., commercial material); noise, which consisted of material that did not fit any of the previous categories; and unavailable, the URLs that could not be reached.…”
Section: Classifying Web Citationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vaughan and Shaw's (2005) follow-up study used their 2003 scheme to classify journal articles from four fields. Kousha and Thelwall (2007) sampled web citations to open-access journals in four fields (biology, physics, chemistry, and computing). Jepsen, Seiden, Ingwersen, Björneborn, and Borlund (2004) classified content from URLs containing specific terms related to plant biology into six categories: scientific, with research-related content (e.g., research articles, preprints); scientifically related (e.g., researchers' CVs); teaching (e.g., textbooks, tutorials, student papers); low grade, which was material that did not belong with the previous groups but was related to the searched topic (e.g., commercial material); noise, which consisted of material that did not fit any of the previous categories; and unavailable, the URLs that could not be reached.…”
Section: Classifying Web Citationsmentioning
confidence: 99%
“…They merged the seven categories into three broader categories: research impact (e.g., in a scholarly article), other intellectual impact (e.g., course reading), and perfunctory (nonintellectual, e.g., an article listed in a bibliography site). Kousha and Thelwall (2007) concluded that "the web provides access to a new and different type of citation information, one that may therefore enable us to measure different aspects of research, and the research process in particular, but in order to obtain good information the different types should be separated" (p. 1631). Kousha and Thelwall (2007) sampled web citations to open-access journals in four fields (biology, physics, chemistry, and computing).…”
Section: Classifying Web Citationsmentioning
confidence: 99%
“…One of the main webometric techniques is impact analysis: using web-based methods to estimate the online impact of documents (Kousha & Thelwall, 2007b;Kousha, Thelwall, & Rezaie, 2010;Vaughan & Shaw, 2005), journals (Smith, 1999;Vaughan & Shaw, 2003), digital repositories (Zuccala, Thelwall, Oppenheim, & Dhiensa, 2007), researchers (Barjak, Li, & Thelwall, 2007;Cronin & Shaw, 2002), research groups (Barjak & Thelwall, 2008), departments (Chen, Newman, Newman, & Rada, 1998;Li, Thelwall, Wilkinson, & Musgrove, 2005b), universities (Aguillo, 2009;Aguillo, Granadino, Ortega, & Prieto, 2006;Qiu, Chen, & Wang, 2004;Smith, 1999), and even countries (Ingwersen, 1998;Thelwall & Zuccala, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It has also become one of the most widely used bibliometric methods (Rubin 2004). The major advantages of citation analysis are its high reliability and unobtrusiveness and that its use for quantitative-driven study differs from conventional research methods, such as participant observation, interviews and questionnaires, in exploring the utilization of academic resources (Kousha and Thelwall 2007). At the same time, the Web has had a huge impact on citation analysis research.…”
Section: Introductionmentioning
confidence: 99%